2015
DOI: 10.1209/0295-5075/112/27001
|View full text |Cite
|
Sign up to set email alerts
|

A new and simple model for magneto-optics uncovers an unexpected spin switching

Abstract: In magneto-optics the spin angular momentum Sz of a sample is indirectly probed by the rotation angle and ellipticity, which are mainly determined by the off-diagonal susceptibility χ (1) xy . A direct and analytic relation between Sz and χ (1) xy is necessary and of paramount importance to the success of magneto-optics, but is often difficult to acquire since quantum mechanically the relation is hidden in the sum-over-states. Here we propose a new and simple model to establish such a much needed relation. Our… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 33 publications
4
36
0
Order By: Relevance
“…This finding appears to agree with the experimental results reasonably well [18]. If the laser field becomes too stronger, we are not completely confident whether our model can describe the physics correctly, though we did test the model in a single site case [24], where we found that the switching becomes highly nonlinear, and even the linearly polarized light can switch the spin. For this reason, our present paper exclusively focuses on the lower laser field limit and ferromagnets.…”
Section: Tb Alloyssupporting
confidence: 74%
“…This finding appears to agree with the experimental results reasonably well [18]. If the laser field becomes too stronger, we are not completely confident whether our model can describe the physics correctly, though we did test the model in a single site case [24], where we found that the switching becomes highly nonlinear, and even the linearly polarized light can switch the spin. For this reason, our present paper exclusively focuses on the lower laser field limit and ferromagnets.…”
Section: Tb Alloyssupporting
confidence: 74%
“…1). We wonder whether our prior model that was developed for all-optical spin switching [37][38][39][40][41] could help. This model is very much similar to the traditional t − J model, where the spin degree of freedom is taken into account by the Heisenberg exchange interaction, and the charge degree of freedom is taken into account by the hopping term between neighboring atoms.…”
Section: Theoretical Formalismmentioning
confidence: 99%
“…When we were investigating the magneto-optical effect, we accidentally discovered a model [19,20] that allows us to simulate spin reversal, without an effective magnetic field. Different from other studies, we augment a spin-orbit coupling term, λL i · S i , to the Heisenberg exchange model, where λ is the spin-orbit coupling constant, L i and S i are the orbital and spin angular momenta at site i.…”
Section: Theoretical Formalismmentioning
confidence: 99%
“…Different from other studies, we augment a spin-orbit coupling term, λL i · S i , to the Heisenberg exchange model, where λ is the spin-orbit coupling constant, L i and S i are the orbital and spin angular momenta at site i. Our Hamiltonian is [15,[19][20][21]…”
Section: Theoretical Formalismmentioning
confidence: 99%
See 1 more Smart Citation